PENERAPAN PEMBELAJARAN PBL UNTUK MENINGKATKAN KOMPETENSI KOMUNIKASI BAHASA INGGRIS MAHASISWA DI AKPARTA MANDALA BAKTI SURAKARTA - Ratini Setyowati; Purwidodo - (Universitas Muhammadiyah Semarang, 2015)
Mastery of foreign languages, especially English is very important for students, but a monotonous learning model making English communication competence of students cannot develop properly. Therefore, researchers are interested in using learning model Problem Based Learning (PBL) for the improvement of communication skills in English. The purpose of this study is to know how big is the influence of the PBL learning model or Problem Based Learning on improving communication competence (Communicative Competence) English students. The method of this study is descriptive qualitative with 32 samples of AKPARTA Mandala Bakti Surakarta students of 2013/2014 academic year. Based on t-test, the result of the research showed that p = 0.00 and r = 0.939 for p <0.05 then Ho is rejected, that means there is a difference between students‟ English competence before applying PBL model on teaching learning process and after applying PBL model for teaching learning process.Key Words: English, Problem Based Learning, Communicative Competence